Tanggung Jawab Pelaku Usaha terhadap Konsumen atas Klausula Eksonerasi dalam Perjanjian Baku - Kiki Riski Kurniasih; Fahmi Fahmi; Yeni Triana (Prodi Ilmu Hukum, Universitas Teuku Umar, 2022)
The emergence of standard agreements is a necessary development in the world of economy which expects all processes to take place quickly and practically. The standard agreement is not prohibited by law, but the use of the Exenation clause is prohibited by law. This article discusses the responsibilities of business actors to consumers in the exoneration clause because business actors transfer responsibility. The aim is to analyze the legal responsibilities and legal consequences of business actors on consumers in the exoneration clause. The research method used is normative with case and analytic approaches. The results showed that the business actor was not responsible because the business actor transferred responsibility, the legal consequence of the transfer of responsibility was the agreement was null and void, could be punished with imprisonment or a fine